PAKISTAN’S PALESTINE POLICY THROUGH THE LENS OF ISLAMIC BROTHERHOOD: A HISTORICAL ANALYSIS - Talha bin Asad; Dr Hafiz Sfarish Ali; Dr Muhammad Waris Ali (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The relationship shared by all humans mutually is brotherhood as per Islamic Teachings outlined in the Quran and the Sunnah of the Prophet PBUH. It is strengthened with faith and renamed as Islamic Brotherhood that requires universality according to which all the Muslims are one Ummah (Community) each member of which is expected to share the joys and sorrows of others. Islamic concept of brotherhood is deeply connected with Palestinian issue in many ways. The Palestinian inquiry figures conspicuously in Pakistan’s foreign policy proclamations, and its leaders consistently express their support for “the just and noble cause of our Palestinian brethren to secure their national right to self-determination and an independent state of their own.’’ From Historical perspective, Pakistan and Israel have not been engaged in any clash with each other. Pakistan has not recognized Israel since its inception because Pakistan has consistently supported Palestine, and it may have fear of Israel and India relations that would ultimately lead to the misbalance of power in Subcontinent. By analysing different viewpoints, this paper will investigate primarily the historical stance of the state of Pakistan on the Palestine issue, since its establishment. After analysing different approaches and considering domestic debates in Pakistan about Palestine issue, this will also contribute whether Pakistan should shift its stance about Israel or otherwise.